Implementação de planos de manutenção para uma linha de envasamento em uma cervejaria dos Campos Gerais (PR) - Fontanini, Ricieri Augusto Mendes (2018)
Maintenance plans consist of a set of activities performed regularly to maintain plant equipment and facilities in the best operational states in order to optimize their overall efficiency, service life and costs related to the interventions. The present work aims to implement maintenance plans for a new bottling line in a brewery in Campos Gerais, state of Paraná, which employs maintenance management practices and the TPM program in search of continuous improvement. The proposed methodology was classified as action research, applied, qualitative and exploratory. The development stages of the study resulted in the registration of the 40 equipment present at the installation site, in addition to 215 maintenance plans, serving 100% of the recommended equipment. Standardization of flows was also obtained to create and revise maintenance plans, defining steps and responsibilities. In this way, the organization demonstrates how maintenance management, in its strategic form, seeks to optimize the efficiency, quality and safety of its facilities, so as to reflect the capacity and availability of the machine, lower maintenance costs and unscheduled downtime, improving the profitability of the business.